A novel mistranslating tRNA model in Drosophila melanogaster has diverse, sexually dimorphic effects. Issue 5 (10th February 2022) - Isaacson, Joshua R; Berg, Matthew D; Charles, Brendan; Jagiello, Jessica; Villén, Judit; Brandl, Christopher J; Moehring, Amanda J
Abstract: Transfer RNAs (tRNAs) are the adaptor molecules required for reading the genetic code and producing proteins. Transfer RNA variants can lead to genome-wide mistranslation, the misincorporation of amino acids not specified by the standard genetic code into nascent proteins. While genome sequencing has identified putative mistranslating transfer RNA variants in human populations, little is known regarding how mistranslation affects multicellular organisms. Here, we create a multicellular model of mistranslation by integrating a serine transfer RNA variant that mistranslates serine for proline (tRNA UGG, G 26 A Ser ) into the Drosophila melanogaster genome. We confirm mistranslation via mass spectrometry and find that tRNA UGG, G 26 A Ser misincorporates serine for proline at a frequency of ∼0.6% per codon. tRNA UGG, G 26 A Ser extends development time and decreases the number of flies that reach adulthood. While both sexes of adult flies containing tRNA UGG, G 26 A Ser present with morphological deformities and poor climbing performance, these effects are more pronounced in female flies and the impact on climbing performance is exacerbated by age. This model will enable studies into the synergistic effects of mistranslating transfer RNA variants and disease-causing alleles.